A MIDDLE BRONZE AGE KURGAN WITH AN EARLY SCYTHIAN COMPLEX IN MOUNTAINOUS ADYGEA - Bakusev, Marat Arturovic; Erlih, Vladimir Roal'dovic; Spasskaa, Natal'a Nikolaevna; Lagoza, Artur Pavlovic (History, Archeology and Ethnography of the Caucasus, 2026)
This article introduces the excavation materials of the Middle Bronze Age kurgan “Deguako-89,” located in the mountainous region of Adygea near the village of Dakhovskaya on the Deguako Plain. Beneath the stone mound of the kurgan, a double burial (Burial 2) of two Middle Bronze Age men was discovered. Due to the absence of grave goods, the burial was dated based on a vessel found in the funeral feast (trizna) remains and the structural characteristics of the stone mound, which has dated analogies across the Deguako Plain. Additionally, an intrusive male burial (Burial 1) from the Early Iron Age was identified within the kurgan. This burial is dated by an iron knife to no earlier than the second half of the 8th century BCE. Associated with the kurgan is an attached ritual complex or horse burial containing the skeletal remains of two or three horses. While these horses may have been sacrificed during the interment of Burial 1, it is also possible they represent a separate commemorative offering at a site already sanctified by human remains. Artifacts recovered from this complex include: two sets of horse harnesses and ring-shaped plaques; arrowheads, spearheads, and a whetstone; beads and the fragmented remains of several ceramic vessels. The materials from the ritual complex/horse burial date to the third quarter of the 7th century BCE. These finds share broad analogies with a wide range of Early Scythian period sites, including those in the Western Caucasus. They attest to the material cultural unity between populations of the foothill and mountain zones, while simultaneously revealing nuanced differences in funerary rites. Furthermore, these findings fill a significant chronological lacuna regarding the Maeotian presence within the “mountainous” variant of Maeotian culture during this period.
Keywords: Mountainous Adygea; kurgan; Middle Bronze Age; Early Scythian period; Maeotians; bridle; horse burials